2021
DOI: 10.3390/biology10090822
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Bacterial Infections in COVID-19 Patients: Antimicrobial Resistance in the Time of SARS-CoV-2

Abstract: The global onset of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus infections happened suddenly, hence imposing a rapid definition of effective therapeutic approaches. Antibiotics were included among the prophylactic agents because of both the similarity between SARS-CoV-2 and atypical pneumonia symptoms, and the immune-modulating and anti-inflammatory properties of such drugs. Although, this approach could exacerbate the emergence of antimicrobial resistance. To evaluate the impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
(35 reference statements)
3
15
1
Order By: Relevance
“…We found that the male COVID-19 patients were signi cantly at risk of bacterial infection as compared to female patients, and this is consistent with other studies that found men to be at risk of having bacterial infections, consequently being severely ill and at increased risk of death Gram-negative bacteria (GNB) isolates were susceptible to Amikacin (AMK) but not Gentamicin (GEN), as opposed to Stephanini et al (2020), who reported high resistance to amikacin among COVID-19 patients [47]. Aminoglycosides contain a defensin-mediated antiviral activity that, through retrocyclins, boosts immunity against SARS-CoV-2 [69].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…We found that the male COVID-19 patients were signi cantly at risk of bacterial infection as compared to female patients, and this is consistent with other studies that found men to be at risk of having bacterial infections, consequently being severely ill and at increased risk of death Gram-negative bacteria (GNB) isolates were susceptible to Amikacin (AMK) but not Gentamicin (GEN), as opposed to Stephanini et al (2020), who reported high resistance to amikacin among COVID-19 patients [47]. Aminoglycosides contain a defensin-mediated antiviral activity that, through retrocyclins, boosts immunity against SARS-CoV-2 [69].…”
Section: Resultssupporting
confidence: 87%
“…[36], Egypt [45], Bahrain [46]and Italy [47]. The predominance of K. pneumoniae and GNB infections in COVID-19 patients is attributable to the microorganisms' ability to acquire different resistance traits [46] and to cause infections in patients with invasive devices and mechanical ventilation during hospitalization [47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To fight the inflammatory syndrome, many immunomodulant agents are used, such as corticosteroids, anti-interleukin-1 (IL-1), anti-interleukin-6 (IL-6), and inhibitors of the JAK-STAT pathway [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The use of immune suppressive drugs, combined with the natural immune suppression caused by the virus, can lead to a surge of secondary bacterial and fungal infections [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%